PENGARUH INKORPORASI METRONIDAZOLE PADA MEMBRAN GELATIN-CHA TERHADAP PROLIFERASI SEL FIBROBLAS (Kajian in vitro dengan MTT assay) - , RADEN REVITA YOSITA IYOS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In dentistry, clinician struggles against anaerobic bacterial infection and to some extent progressive alveolar destruction such as in periodontitis. Controlled release technology, known as drug delivery system, using carbonate apatite (CHA) graft may solve the problems related to alveolar bone resorption caused by periodontitis. The aim of this research was to investigate the influence of metronidazole incorporation into gelatin-CHA membrane on the fibroblast proliferation. Metronidazole solution in 0,05, 0,1 and 0,2 % (3 Î¼L) were incorporated into gelatin-CHA membrane with 5 mm diameter. The gelatin-CHA membranes incorporated with metronidazole as well as gelatin-CHA membarane without metronidazole were cultivated in fibroblast cells. Fibroblast proliferation was observed after 24, 48 and 72 hours cultivation using MTT assay at 550 nm and light microscopy. The optical density obtained from MTT assay was analyzed statistically using One-way Analysis of Variance. The results show that there were no significant differences on fibroblast proliferation with or without incorporation of metronidazole (p>0,05). The increased concentration of metronidazole loaded into gelatin-CHA membranes did not affect the rate of fibroblast proliferation, showing that optimum dosage of metronidazole for periodontitis treatment may be achieved by DDS technology. Further investigation is needed to measure optimum capacity of gelatin-CHA membranes to load metronidazole.